Detection and Molecular Characterization of Salmonella enterica Serovar Eppendorf Circulating in Chicken Farms in Tunisia. (5th November 2015) - Ben Salem, R.; Abbassi, M.S.; García, V.; García‐Fierro, R.; Njoud, C.; Messadi, L.; Rodicio, M. R.
Summary: Salmonella enterica subsp. enterica serovar Eppendorf, with antigenic formula 1, 4, 12, [27]:d:1, 5, is an infrequent serovar. However, 14% (20 of 142) of the isolates recovered during June–July 2012 in chicken farms in Tunisia belonged to S . Eppendorf. These isolates were analysed for resistance and virulence profiles. None of them were susceptible to all antimicrobials tested, while 70%, 60%, 50%, 50%, 20% and 5% were resistant to sulphonamides ( sul1, sul2 and sul3 ), streptomycin ( aadA1 ‐like), trimethoprim ( dfrA1 ‐like), nalidixic acid (GyrA Asp87 →Asn and not identified), gentamicin (not identified) and ampicillin ( bla TEM ‐1‐like). About 30% of the isolates showed decreased susceptibility to ciprofloxacin and carried the qnrB gene; 65% of the isolates were multidrug resistant and contained class 1 integrons with sul1 or sul3 in the 3′ conserved segment. The orgA, ssaQ, mgtC, siiD and sopB virulence genes located on SPI1 to SPI5 and the fimbrial bcfC gene were present in all isolates; the sopE1 and sodC1 carried by prophages were variably detected; however, the prophage gipA gene and the spvC gene of serovar‐specific virulence plasmids were absent. Altogether, ten resistance and three virulence profiles were identified. Typing of the isolates with Xba I‐ and Bln I‐PFGE supports a close relationship, although they appear to be evolving under selective pressure probably caused by antimicrobial use in chicken husbandry. As far as we know, this is the first study investigating the molecular bases of antimicrobial drug resistance, the virulence gene content and the PFGE profiles of S . Eppendorf. The epidemiological surveillance of this serovar would be necessary to evaluate its possible impact on human health, particularly in Tunisia and other African countries where it was already reported.